Larval morphology and complex vocal repertoire of Rhacophorus helenae (Anura: Rhacophoridae), a rare flying frog from Vietnam - Vassilieva, Anna B.; Gogoleva, Svetlana S.; Poyarkov, Nikolay A. Jr. (Zootaxa, 2016)
We present new data on the distribution, reproduction, larval morphology and vocalization of Rhacophorus helenae (Rhacophoridae), a narrowly distributed frog from southern Vietnam. Two new populations of R. helenae were discovered during field surveys in the lowland monsoon forests in Dong Nai and Ba Ria–Vung Tau provinces in 2010–2013. Spawning was observed in May 2013. Egg clutches containing small (2.3±0.1 mm) unpigmented eggs were embedded in a foam nest and suspended high on trees above temporary ponds. The tadpoles of R. helenae have a morphology typical of pond-dwelling Rhacophorus larvae with a moderate tail length and a labial tooth row formula of 5(2–5)/3. Postmetamorphic juveniles differed from adult frogs in the features of their coloration and less developed webbing. The complex vocal repertoire of R. helenae included five types of tonal, wideband and pulsed calls and several transitional signal types differentiated by frequency and amplitude parameters. Calls were uttered as singular signals (pulsed calls) or within non-stereotyped series of variable duration (other call types). The complex structure of the advertisement call markedly distinguishes R. helenae from other members of the Rhacophorus reinwardtii species complex.